Down‐regulation of ATF1 leads to early neuroectoderm differentiation of human embryonic stem cells by increasing the expression level of SOX2. Issue 9 (26th June 2019) - Yang, Shang‐Chih; Liu, Jan‐Jan; Wang, Cheng‐Kai; Lin, Yu‐Tsen; Tsai, Su‐Yi; Chen, Wei‐Ju; Huang, Wei‐Kai; Tu, Po‐Wen A.; Lin, Yu‐Chen; Chang, Ching‐Fang; Cheng, Chih‐Lun; Lin, Hsuan; et al.
ABSTRACT: We reveal by high‐throughput screening that activating transcription factor 1 (ATF1) is a novel pluripotent regulator in human embryonic stem cells (hESCs). The knockdown of ATF1 expression significantly up‐regulated neuroectoderm (NE) genes but not mesoderm, endoderm, and trophectoderm genes. Of note, down‐regulation or knockout of ATF1 with short hairpin RNA (shRNA), small interfering RNA (siRNA), or clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9) was sufficient to up‐regulate sex‐determining region Y‐box (SOX)2 and paired box 6 (PAX6) expression under the undifferentiated or differentiated conditions, whereas overexpression of ATF1 suppressed NE differentiation. Endogenous ATF1 was spontaneously down‐regulated after d 1–3 of neural induction. By double‐knockdown experiments, up‐regulation of SOX2 was critical for the increase of PAX6 and SOX1 expression in shRNA targeting Atf1 hESCs. Using the luciferase reporter assay, we identified ATF1 as a negative transcriptional regulator of Sox2 gene expression. A novel function of ATF1 was discovered, and these findings contribute to a broader understanding of the very first steps in regulating NE differentiation in hESCs.—Yang, S.‐C, Liu, J.‐J., Wang, C.‐K., Lin, Y.‐T., Tsai, S.‐Y., Chen, W.‐J., Huang, W.‐K., Tu, P.‐W. A., Lin, Y.‐C, Chang, C.‐F., Cheng, C.‐L., Lin, H., Lai, C.‐Y., Lin, C.‐Y., Lee, Y.‐H., Chiu, Y.‐C., Hsu, C.‐C., Hsu, S.‐C., Hsiao, M., Schuyler, S. C., Lu, F. L., Lu, J. Down‐regulation of ATF1 leads to early neuroectoderm differentiation of human embryonic stem cells by increasing the expression level of SOX2. FASEB J. 33, 10577–10592 (2019). www.fasebj.org